INTEGRASI MODEL DEEP LEARNING DALAM INOVASI PEMBELAJARAN PAI UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS DAN KESADARAN SPIRITUAL SISWA SMA - Anifatur Rahmawati; Achmad Yusuf; Ahmad Marzuki; Muhammad Nur Hadi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Balancing the strengthening of critical thinking and the formation of spiritual awareness in Islamic Religious Education (PAI) still presents a tension between content mastery orientation and students’ reflective depth. In many classroom practices, learning processes have not yet fully provided space for the elaboration of learning experiences, deep reasoning, and the internalization of religious values in everyday life. This study aims to examine the implementation of deep learning in PAI through a qualitative case study approach in an educational setting that applies reflection-based learning. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, presentation, and thematic meaning-making. The findings indicate that the learning process is shaped by the teacher’s role as a facilitator, student-centered learning, the use of technology as a learning resource, and the strengthening of reflective activities such as muhasabah. This approach fosters the development of critical thinking skills while simultaneously deepening students’ spiritual awareness through the internalization of religious values in contextual situations. Overall, the implementation of deep learning contributes to a more meaningful, participatory, and holistic Islamic Religious Education learning experience. ABSTRAK Upaya menyeimbangkan penguatan berpikir kritis dan pembentukan kesadaran spiritual dalam pembelajaran Pendidikan Agama Islam (PAI) masih menghadapi ketegangan antara orientasi penguasaan materi dan kedalaman reflektif siswa. Di banyak praktik kelas, proses pembelajaran belum sepenuhnya memberi ruang bagi elaborasi pengalaman belajar, penalaran mendalam, serta internalisasi nilai keagamaan dalam kehidupan sehari-hari. Penelitian ini bertujuan untuk memotret penerapan deep learning dalam pembelajaran PAI melalui pendekatan studi kasus kualitatif pada satuan pendidikan yang mengembangkan pembelajaran berbasis refleksi. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis melalui tahapan reduksi, penyajian, dan penarikan makna secara tematik. Hasil penelitian menunjukkan bahwa pembelajaran berlangsung melalui peran guru sebagai fasilitator, pembelajaran berpusat pada siswa, pemanfaatan teknologi sebagai sumber belajar, serta penguatan aktivitas reflektif seperti muhasabah. Pendekatan ini mendorong berkembangnya kemampuan berpikir kritis sekaligus memperdalam kesadaran spiritual siswa melalui penghayatan nilai agama dalam konteks kehidupan. Secara keseluruhan, deep learning berkontribusi pada pembelajaran PAI yang lebih bermakna, partisipatif, dan holistik.